Influence of mixed convection in atmospheric pressure chemical vapor deposition of graphene growth - Fauzi, Fatin Bazilah; Ismail, Edhuan; Osman, Muhammad Naqib; Rosli, Muhammad Suffian; Ismail, Ahmad Faris; Mohamed, Mohd Ambri; Syed Abu Bakar, Syed Noh; Ani, Mohd Hanafi (Science Direct, 2019)
Chemical vapor deposition (CVD) is a well-known process as the most favourable for high-quality large area graphene production. However, it is a complex method where each parameter will contribute to significant effect on the deposition process. One of them, fluid dynamics, was reported to be one of the major governing factors for better deposition. Heat transfer process at high temperature will influence gas phase dynamics during the deposition process. In this study, the influence of mixed convection in atmospheric pressure CVD (APCVD) on the graphene quality has been systematically investigated. Reynolds number was calculated to identify the gas flow regime as well as to see its effects on the graphene quality. Then, the type of dominant convection inside the reactor was determined using Richardson number (Grashof number/Reynolds number squared). Changes in graphene quality were then observed by Raman spectra at various values of Reynolds and Richardson numbers. Additionally, computational fluid dynamics (CFD) calculations were also performed to observe the temperature and velocity contour during deposition. We then discuss the vital thermal-fluid dynamic characteristics required for an optimal graphene growth. We highlighted that a force convection in APCVD was vital for better quality of graphene.